The biomechanical characteristics of fencing lunge movements and their implications for physical training - Wei, Shen; Wei, Dongyuan (Molecular & Cellular Biomechanics, 2024)
Fencing is a unique combat sport characterized by its dynamic movements, strategic interactions, and the need for rapid decision-making. Central to a fencer’s performance is the lunge, a foundational movement that enables athletes to engage their opponent effectively while maintaining balance and control. It executes precise and explosive movements, particularly during lunges, which are critical for both offensive and defensive strategies. Understanding the biomechanical characteristics of this action is critical for maximizing performance, improving training regimens, and lowering injury risk. The objective of this study is to investigate the biomechanical characteristics of fencing lunge movements and their implications for physical training. A total of 126 fencers participated in this study. They are randomly divided into two groups: Group A, who received physical training based on biomechanical intervention, and Group B, who received traditional physical training. Using motion capture data through cameras, sensors and force plates, the lunge technique of competitive fencers is analyzed, examining variables such as joint angles, force application, and ground reaction forces. The data analysis and statistical methods include descriptive statistics, t-tests, and ANOVA to identify significant differences between the groups. The findings demonstrate Group A significantly improved the optimal lunge execution, which is characterized by specific patterns of joint movement, particularly at the ankle, knee, and hip, which correlate with successful reach and stability. Also, Group A identified the importance of muscular strength, flexibility, and reaction time in enhancing lunge performance to Group B. The study describes that integrating these biomechanical concepts into training programs, coaches, and players can enhance performance, reduce the risk of injury, and encourage long-term fencing success.